Persepsian risiko, kepuasan, citra harga dan niat beli ulang menggunakan m-commerce: Peran kepercayaan dan sensitifitas harga sebagai pemoderasi - Verselly Nisaa; Perengki Susanto (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2021)
This study aims to examine the effect of perceived risk, satisfaction, and price image on repurchase intention using m-commerce. The role of trust and price sensitivity as moderators is also examined in this study. Customers who used m-commerce for shopping in a West Sumatra region were surveyed. A total of 290 samples were used in the data analysis. With the support of SmartPLS version 3.0, data analysis was carried out utilizing the Partial Least Square-Structural Equation Model (PLS-SEM) approach. The findings revealed that repurchase intention was influenced by satisfaction and price image. Perceived risk, on the other hand, has no effect on repurchase intention. Furthermore, neither the effect of perceived risk nor the effect of price image on repurchase intention is moderated by trust or price sensitivity. M-commerce operators can learn from this study that the notion of risk in using m-commerce for shopping is no longer.Keywords: M-commerce; perceived risk; satisfaction; price image; repurchase intention. TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//